Polypropylene quantum dot diffusion plate and preparation method thereof

By adopting a three-layer structure in the polypropylene quantum dot diffusion plate, using nano microspheres and ammonium polyphosphate to improve flame retardancy, and improving optical performance by surface carboxylation of oil-soluble CdSe/ZnS quantum dots and PP-g-MAH resin, the problems of poor flammability and optical performance of the polypropylene quantum dot diffusion plate in the prior art are solved, and high water oxygen barrier properties and overall structural stability are achieved.

CN119773333AInactive Publication Date: 2025-04-08REGENCY OPTICS ELECTRON CORP
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510037014.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-04-08
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing polypropylene quantum dot diffusion plates have decreased quantum efficiency during high-temperature treatment, and have poor flammability and optical performance, making it difficult to disperse evenly in polymer materials.

Method used

A three-layer structure polypropylene quantum dot diffusion plate is adopted, nano microspheres and ammonium polyphosphate are added to the upper and lower layers to improve flame retardancy, and surface carboxylated oil-soluble CdSe/ZnS quantum dots and PP-g-MAH resin are added to improve optical performance, and quantum dots are physically isolated through the "sandwich" structure.

Benefits of technology

The polypropylene quantum dot diffusion plate with high water oxygen barrier properties, high flame retardancy and optical properties has been achieved. The overall structure is stable, avoiding the problem of quantum dots being inactivated at high temperatures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005235814600000111
    Figure BDA0005235814600000111
Patent Text Reader

Abstract

The invention discloses a polypropylene quantum dot diffusion plate and a preparation method thereof.The polypropylene quantum dot diffusion plate comprises an upper layer, a middle layer and a lower layer, the upper layer and the lower layer are located on the two sides of the middle layer, and the upper layer and the lower layer are the same in composition; the upper layer comprises the following components: polypropylene resin, nano microspheres, ammonium polyphosphate, pentaerythritol, an antioxidant, mineral oil, a hindered amine light stabilizer, an ultraviolet light absorber and a whitening agent; the middle layer is prepared from the following components: polypropylene resin, PP-g-MAH resin, surface carboxylation oil-soluble CdSe / ZnS quantum dots, an antioxidant, mineral oil, a hindered amine light stabilizer, an ultraviolet light absorber and a whitening agent; the diffusion plate prepared by the invention has the advantages of high water and oxygen barrier property, high flame retardance, good optical performance, stable overall structure and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of optical diffusion plate manufacturing, in particular to a polypropylene quantum dot diffusion plate and a preparation method thereof. Background Art

[0002] Polypropylene (PP) resin is a general-purpose thermoplastic obtained by polymerization of propylene. Due to its abundant raw material sources and simple synthesis process, compared with other general-purpose thermoplastics, it has the characteristics of low price, good electrical insulation, chemical corrosion resistance, easy processing, non-toxicity, high transparency, and low specific gravity. Therefore, it is widely used in the automotive, electrical, packaging and daily necessities industries. However, polypropylene resin is a flammable plastic, and it releases a lot of heat during combustion, which causes dripping and spread of fire. There are great safety hazards during use.

[0003] Quantum dots are a type of nanoscale semiconductor material that can emit light of a specific frequency by applying an electric field or light pressure. Existing technologies often combine quantum dot technology with light diffusers to make quantum dot diffusers. However, quantum dots are very sensitive to heat, oxygen and water, which poses challenges to their application in polymer materials, including difficulty in evenly dispersing them in polymer masterbatches and decreased quantum efficiency during high-temperature treatment.

[0004] Directly mixing quantum dots into polypropylene resin to prepare a diffusion plate, since quantum dots cannot be stably and evenly dispersed in polypropylene resin all the time, the diffusion plate will experience brightness decay and poor luminous efficiency as the quantum dots become inactive, and this type of diffusion plate also inherits the flammability disadvantage of polypropylene resin itself. Therefore, how to combine polypropylene with quantum dots to prepare a polypropylene quantum dot diffusion plate with high water and oxygen barrier properties, high flame retardancy, good optical properties, and overall stable structure is a topic worth studying, but no reports on this have been seen so far. Summary of the invention

[0005] In order to solve the above problems, the present invention provides a polypropylene quantum dot diffusion plate with a stable overall structure, good optical properties, high water and oxygen barrier properties and high flame retardancy, comprising an upper layer, an intermediate layer and a lower layer, wherein the upper layer and the lower layer are located on both sides of the intermediate layer, and the upper layer and the lower layer have the same components, and the upper layer comprises the following components by mass: 61 to 79 parts of polypropylene resin, 7 to 13 parts of nano-microspheres, 10 to 16 parts of ammonium polyphosphate, 1 to 3 parts of pentaerythritol, 1 to 1.8 parts of antioxidant, 0.5 to 1.5 parts of mineral oil, 0. 6 to 1.2 parts of hindered amine light stabilizer, 0.4 to 1 parts of ultraviolet absorber, and 0.5 to 1.5 parts of brightener; the middle layer includes the following components in parts by mass: 66 to 82 parts of polypropylene resin, 11 to 19 parts of PP-g-MAH resin, 5 to 9 parts of surface carboxylation oil-soluble CdSe / ZnS quantum dots, 0.3 to 0.7 parts of antioxidant, 0.6 to 1.6 parts of mineral oil, 0.4 to 1.2 parts of hindered amine light stabilizer, 0.2 to 1 parts of ultraviolet absorber, and 0.5 to 1.5 parts of brightener.

[0006] Preferably, the antioxidant is any one of antioxidant 1024, antioxidant 1010 or antioxidant 1076.

[0007] Preferably, the mineral oil is silicone oil or liquid paraffin.

[0008] Preferably, the hindered amine light stabilizer is any one selected from light stabilizer 622, light stabilizer 770, and light stabilizer 944.

[0009] Preferably, the ultraviolet absorber is selected from any one of ultraviolet absorbers UV-327, UV-329, and UV-531.

[0010] Preferably, the brightener is fluorescent brightener CBS-127.

[0011] The present invention also provides a method for preparing a polypropylene quantum dot diffusion plate, comprising the following steps:

[0012] Preparation of nanoparticles;

[0013] 7 to 13 parts of nanospheres, 61 to 79 parts of polypropylene resin, 10 to 16 parts of ammonium polyphosphate, 1 to 3 parts of pentaerythritol, 1 to 1.8 parts of antioxidant, 0.5 to 1.5 parts of mineral oil, 0.6 to 1.2 parts of hindered amine light stabilizer, 0.4 to 1 parts of ultraviolet absorber, and 0.5 to 1.5 parts of brightener are uniformly mixed to obtain a mixture a;

[0014] 5 to 9 parts of surface carboxylated oil-soluble CdSe / ZnS quantum dots, 66 to 82 parts of polypropylene resin, 11 to 19 parts of PP-g-MAH resin, 0.3 to 0.7 parts of antioxidant, 0.6 to 1.6 parts of mineral oil, 0.4 to 1.2 parts of hindered amine light stabilizer, 0.2 to 1 parts of ultraviolet absorber, and 0.5 to 1.5 parts of brightener are uniformly mixed to obtain a mixture b;

[0015] Mixture a and mixture b are put into a single screw extruder in a mass ratio of (2-6):1, heated and melted, three-layer co-extruded and embossed to obtain a finished product;

[0016] Among them, the temperatures of each zone of the single-screw extruder are: zone one temperature is 180-190°C, zone two temperature is 190-200°C, zone three temperature is 210-220°C, zone four temperature is 210-220°C, zone five temperature is 225-235°C, zone six temperature is 215-225°C, zone seven temperature is 210-220°C, and the die head temperature is 205-215°C; the production speed is 310kg / h.

[0017] Preferably, the preparation of nano microspheres comprises the following steps: adding 100 parts of water to a container, adding 0.1-0.3 parts of sodium hydroxide to adjust the pH to 10-12, heating in a water bath to 50-60° C., adding 0.05-0.15 parts of decyl glucoside, adding vinyl trimethoxysilane dropwise at a rate of 3-5 drops / s for 5-10 minutes while stirring, then adding 10-50 drops of 10-20wt% acetic acid solution, standing, centrifuging and collecting the precipitate, washing the filter residue with deionized water and anhydrous ethanol for several times until neutral, and drying to obtain nano vinyl silicone resin microspheres; placing 10-30 parts of nano vinyl silicone resin microspheres in 100 parts of anhydrous ethanol for ultrasonication for 20-40 minutes, The nano vinyl silicone resin microspheres are uniformly dispersed in anhydrous ethanol, 0.1-0.3 parts of benzoin dimethyl ether are added, the benzoin dimethyl ether is stirred to dissolve, 3-9 parts of thioglycolic acid are added, the mixture is stirred for 10-20 minutes under ultraviolet light, the precipitate is collected by centrifugation, the filter residue is washed several times with deionized water and anhydrous ethanol respectively until it is neutral, and the mixture is dried to obtain carboxylated nano vinyl silicone resin microspheres; 10-20 parts of cobalt acetate are added to 100 parts of water, 3-9 parts of carboxylated nano vinyl silicone resin microspheres are added to the water, ultrasonic treatment is performed for 20-40 minutes, the precipitate is collected by centrifugation, the filter residue is washed several times with deionized water and anhydrous ethanol respectively until it is neutral, and the mixture is dried to obtain nano microspheres.

[0018] Preferably, the centrifugal speed is 8000-10000 r / min, and the centrifugal time is 10-20 min.

[0019] Preferably, the drying temperature is 80-90° C. and the drying time is 6-8 hours.

[0020] The beneficial effect is as follows: the present application provides a polypropylene quantum dot diffusion plate, including three layers: upper, middle and lower. The nano-microspheres added to the upper and lower layers have high flame retardancy due to the silicon and cobalt elements, and the flame retardancy of the upper and lower layers is further improved by combining with ammonium polyphosphate. When the diffusion plate burns, the side chains on the surface of the silicon- and cobalt-containing nano-microspheres decompose, and the cobalt is oxidized into cobalt oxide during the combustion process. The cobalt oxide can cross-link with ammonium polyphosphate to increase the stability of ammonium polyphosphate and reduce the volatilization of phosphorus during the thermal degradation of ammonium polyphosphate. At the same time, the cobalt oxide itself can dehydrogenate, oxidize and phosphate polypropylene to form unsaturated bonds, and further dehydrogenate to form a dense carbon layer. In this way, only the external side chains of the diffusion plate decompose during the combustion process, and the nano-microspheres are retained in the carbon layer, covering the surface of the polypropylene resin, playing an insulating role and preventing the diffusion plate from further burning.

[0021] In order to improve the light diffusion effect of the middle layer, the present application intends to add quantum dots, but the compatibility of ordinary quantum dots with polypropylene resin is extremely poor. For this reason, the present application selects surface carboxylation oil-soluble CdSe / ZnS quantum dots, and adds PP-g-MAH resin for use. The anhydride groups on the PP-g-MAH resin react with the carboxyl groups of the surface carboxylation oil-soluble CdSe / ZnS quantum dots to form ester bonds or amide bonds. At the same time, the polypropylene segments in the PP-g-MAH resin can generate strong interaction forces with the polypropylene matrix through physical entanglement, so that the compatibility of the surface carboxylation oil-soluble CdSe / ZnS quantum dots with polypropylene can be improved, so that the surface carboxylation oil-soluble CdSe / ZnS quantum dots can form a better dispersion in the polypropylene resin, so that the entire middle layer diffusion plate has excellent optical properties and more uniform light emission;

[0022] Arranging the upper and lower layers on both sides of the middle layer to form a "sandwich" structure can physically isolate the quantum dots and reduce the impact of the external environment on the quantum dots, so that the entire diffuser has the advantages of high water and oxygen barrier properties, high flame retardancy, good optical properties and overall structural stability. DETAILED DESCRIPTION

[0023] The present invention is further described in detail below in conjunction with specific embodiments so that those skilled in the art can understand the present invention more clearly.

[0024] The following embodiments are only used to illustrate the present invention, but are not limited to the scope of the present invention. Based on the specific embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without creative work belong to the protection scope of the present invention.

[0025] In the examples of the present invention, unless otherwise specified, all raw material components are commercially available products well known to those skilled in the art; in the examples of the present invention, unless otherwise specified, the technical means used are conventional means well known to those skilled in the art.

[0026] Source of raw materials:

[0027] Polypropylene (PP) resin, model M60ET, purchased from Zhenhai Refining and Chemical Company of Sinopec;

[0028] Ammonium polyphosphate, purchased from Zhenjiang Xingxing Flame Retardant Co., Ltd.;

[0029] Pentaerythritol was purchased from Shanghai Lingfeng Chemical Reagent Co., Ltd.

[0030] Antioxidants were purchased from Shandong Xuxiang Chemical Co., Ltd.

[0031] Silicone oil was purchased from Jinan Xuchuang Chemical Technology Co., Ltd.

[0032] Liquid paraffin was purchased from Hefeng New Energy Co., Ltd.;

[0033] Hindered amine light stabilizer, purchased from Shanghai Tiandui New Materials Co., Ltd.;

[0034] Ultraviolet absorber, purchased from Jinan Xiangfeng Weiye Chemical Co., Ltd.;

[0035] Fluorescent brightener, model CBS-127, purchased from Guangzhou Yuanda New Materials Co., Ltd.;

[0036] Polypropylene grafted maleic anhydride (PP-g-MAH) resin, model Mitsui ADMER, Japan, purchased from Jiangsu Weirun High Plastic Chemical Co., Ltd.;

[0037] Surface carboxylation oil-soluble CdSe / ZnS quantum dots were purchased from Shanghai Shuna Biotechnology Co., Ltd.;

[0038] Sodium hydroxide was purchased from Nanjing Chemical Reagent Co., Ltd.;

[0039] Decyl glucoside was purchased from Shandong New Kinetic Energy Chemical Co., Ltd.;

[0040] Vinyltrimethoxysilane, model A-171, purchased from Nanjing Wanda Silicon Industry Co., Ltd.;

[0041] Acetic acid, anhydrous ethanol, thioglycolic acid, and cobalt acetate were purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0042] Benzoin dimethyl ether was purchased from Nanjing Wali Chemical Co., Ltd.;

[0043] The remaining reagents are commercially available.

[0044] Example 1

[0045] The present embodiment provides a polypropylene quantum dot diffusion plate, comprising an upper layer, a middle layer and a lower layer, the upper layer and the lower layer are located on both sides of the middle layer, the upper layer and the lower layer have the same components, the upper layer comprises the following components in parts by mass: 79 parts of polypropylene resin, 7 parts of nano-microspheres, 10 parts of ammonium polyphosphate, 1 part of pentaerythritol, 1 part of antioxidant, 0.5 parts of mineral oil, 0.6 parts of hindered amine light stabilizer, 0.4 parts of ultraviolet absorber, and 0.5 parts of brightener; the middle layer comprises the following components in parts by mass: 82 parts of polypropylene resin, 11 parts of PP-g-MAH resin, 5 parts of surface carboxylation oil-soluble CdSe / ZnS quantum dots, 0.3 parts of antioxidant, 0.6 parts of mineral oil, 0.4 parts of hindered amine light stabilizer, 0.2 parts of ultraviolet absorber, and 0.5 parts of brightener. The antioxidant is antioxidant 1024, the mineral oil is silicone oil, the hindered amine light stabilizer is light stabilizer 622, the ultraviolet absorber is ultraviolet absorber UV-327, and the brightener is fluorescent brightener CBS-127.

[0046] The method for preparing a polypropylene quantum dot diffusion plate comprises the following steps:

[0047] Preparation of nano-microspheres: adding 100 parts of water to a container, adding 0.1 parts of sodium hydroxide to adjust the pH to 10, heating in a water bath to 50°C, adding 0.05 parts of decyl glucoside, adding vinyl trimethoxysilane at a rate of 3 drops / s for 5 minutes while stirring, and then adding 10 drops of 20wt% acetic acid solution, standing, centrifuging and collecting the precipitate, the centrifugal speed is 8000r / min, the centrifugal time is 10 minutes, washing the filter residue with deionized water and anhydrous ethanol for several times until neutral, drying to obtain nano-vinyl silicone resin microspheres, the drying temperature is 80°C, and the drying time is 6 hours; placing 10 parts of nano-vinyl silicone resin microspheres in 100 parts of anhydrous ethanol and ultrasonicating for 20 minutes to make the nano-vinyl silicone resin microspheres uniformly dispersed in the anhydrous ethanol, adding 0.1 parts of benzoin dimethicone methyl ether, stirring to dissolve benzoin dimethyl ether, then adding 3 parts of thioglycolic acid, stirring under ultraviolet light for 10 minutes, centrifuging and collecting the precipitate, the centrifugal speed is 8000r / min, the centrifugal time is 10min, washing the filter residue with deionized water and anhydrous ethanol for several times until neutral, drying to obtain carboxylated nano vinyl silicone resin microspheres, the drying temperature is 80℃, and the drying time is 6h; adding 10 parts of cobalt acetate to 100 parts of water, and then adding 3 parts of carboxylated nano vinyl silicone resin microspheres to the water, ultrasonicating for 20 minutes, centrifuging and collecting the precipitate, the centrifugal speed is 8000r / min, the centrifugal time is 10min, washing the filter residue with deionized water and anhydrous ethanol for several times until neutral, drying to obtain nano microspheres, the drying temperature is 80℃, and the drying time is 6h;

[0048] 7 parts of the above nanospheres are mixed with 79 parts of polypropylene resin, 10 parts of ammonium polyphosphate, 1 part of pentaerythritol, 1 part of antioxidant, 0.5 parts of mineral oil, 0.6 parts of hindered amine light stabilizer, 0.4 parts of ultraviolet absorber and 0.5 parts of brightener to obtain a mixture a;

[0049] 5 parts of surface carboxylated oil-soluble CdSe / ZnS quantum dots, 82 parts of polypropylene resin, 11 parts of PP-g-MAH resin, 0.3 parts of antioxidant, 0.6 parts of mineral oil, 0.4 parts of hindered amine light stabilizer, 0.2 parts of ultraviolet absorber, and 0.5 parts of brightener are mixed to obtain a mixture b;

[0050] The mixture a and the mixture b are put into a single screw extruder in a mass ratio of 2:1, heated and melted, three-layer co-extruded and embossed to obtain a finished product;

[0051] Among them, the temperatures of each zone of the single-screw extruder are: zone 1 temperature is 180°C, zone 2 temperature is 190°C, zone 3 temperature is 210°C, zone 4 temperature is 210°C, zone 5 temperature is 225°C, zone 6 temperature is 215°C, zone 7 temperature is 210°C, and the die head temperature is 205°C; the production speed is 310kg / h.

[0052] Example 2

[0053] The present embodiment provides a polypropylene quantum dot diffusion plate, comprising an upper layer, a middle layer and a lower layer, the upper layer and the lower layer are located on both sides of the middle layer, the upper layer and the lower layer have the same components, the upper layer comprises the following components in parts by mass: 70 parts of polypropylene resin, 10 parts of nano-microspheres, 13 parts of ammonium polyphosphate, 2 parts of pentaerythritol, 1.4 parts of antioxidant, 1 part of mineral oil, 0.9 parts of hindered amine light stabilizer, 0.7 parts of ultraviolet absorber, and 1 part of brightener; the middle layer comprises the following components in parts by mass: 74 parts of polypropylene resin, 15 parts of PP-g-MAH resin, 7 parts of surface carboxylation oil-soluble CdSe / ZnS quantum dots, 0.5 parts of antioxidant, 1.1 parts of mineral oil, 0.8 parts of hindered amine light stabilizer, 0.6 parts of ultraviolet absorber, and 1 part of brightener. The antioxidant is antioxidant 1010, the mineral oil is liquid paraffin, the hindered amine light stabilizer is light stabilizer 770, the ultraviolet absorber is ultraviolet absorber UV-329, and the brightener is fluorescent brightener CBS-127.

[0054] The method for preparing a polypropylene quantum dot diffusion plate comprises the following steps:

[0055] Preparation of nano-microspheres: adding 100 parts of water to a container, adding 0.2 parts of sodium hydroxide to adjust the pH to 11, heating in a water bath to 55°C, adding 0.1 parts of decyl glucoside, adding vinyl trimethoxysilane at a rate of 4 drops / s for 8 minutes while stirring, and then adding 30 drops of 15wt% acetic acid solution, standing, centrifuging and collecting the precipitate, the centrifugal speed is 9000r / min, the centrifugal time is 15min, washing the filter residue with deionized water and anhydrous ethanol for several times until neutral, drying to obtain nano-vinyl silicone resin microspheres, the drying temperature is 85°C, and the drying time is 7h; placing 20 parts of nano-vinyl silicone resin microspheres in 100 parts of anhydrous ethanol and ultrasonicating for 30 minutes to uniformly disperse the nano-vinyl silicone resin microspheres in the anhydrous ethanol, adding 0.2 parts of benzoin dimethoxybenzyl alcohol ether, stirring to dissolve benzoin dimethyl ether, then adding 6 parts of thioglycolic acid, stirring under ultraviolet light for 15 minutes, centrifuging and collecting the precipitate, the centrifugal speed is 9000r / min, the centrifugal time is 15min, washing the filter residue with deionized water and anhydrous ethanol for several times until neutral, drying to obtain carboxylated nano vinyl silicone resin microspheres, the drying temperature is 85℃, and the drying time is 7h; adding 15 parts of cobalt acetate to 100 parts of water, and then adding 6 parts of carboxylated nano vinyl silicone resin microspheres to the water, ultrasonicating for 30 minutes, centrifuging and collecting the precipitate, the centrifugal speed is 9000r / min, the centrifugal time is 15min, washing the filter residue with deionized water and anhydrous ethanol for several times until neutral, drying to obtain nano microspheres, the drying temperature is 85℃, and the drying time is 7h;

[0056] 10 parts of the nanospheres are mixed with 70 parts of polypropylene resin, 13 parts of ammonium polyphosphate, 2 parts of pentaerythritol, 1.4 parts of antioxidant, 1 part of mineral oil, 0.9 parts of hindered amine light stabilizer, 0.7 parts of ultraviolet absorber and 1 part of brightener to obtain a mixture a;

[0057] 7 parts of surface carboxylated oil-soluble CdSe / ZnS quantum dots, 74 parts of polypropylene resin, 15 parts of PP-g-MAH resin, 0.5 parts of antioxidant, 1.1 parts of mineral oil, 0.8 parts of hindered amine light stabilizer, 0.6 parts of ultraviolet absorber and 1 part of brightener are mixed to obtain a mixture b;

[0058] The mixture a and the mixture b are put into a single screw extruder in a mass ratio of 4:1, heated and melted, three-layer co-extruded and embossed to obtain a finished product;

[0059] Among them, the temperatures of each zone of the single-screw extruder are: zone 1 temperature is 185°C, zone 2 temperature is 195°C, zone 3 temperature is 215°C, zone 4 temperature is 215°C, zone 5 temperature is 230°C, zone 6 temperature is 220°C, zone 7 temperature is 215°C, and the die head temperature is 210°C; the production speed is 310kg / h.

[0060] Example 3

[0061] The present embodiment provides a polypropylene quantum dot diffusion plate, comprising an upper layer, a middle layer and a lower layer, the upper layer and the lower layer are located on both sides of the middle layer, the upper layer and the lower layer have the same components, the upper layer comprises the following components in parts by mass: 61 parts of polypropylene resin, 13 parts of nano-microspheres, 16 parts of ammonium polyphosphate, 3 parts of pentaerythritol, 1.8 parts of antioxidant, 1.5 parts of mineral oil, 1.2 parts of hindered amine light stabilizer, 1 part of ultraviolet absorber, and 1.5 parts of brightener; the middle layer comprises the following components in parts by mass: 66 parts of polypropylene resin, 19 parts of PP-g-MAH resin, 9 parts of surface carboxylation oil-soluble CdSe / ZnS quantum dots, 0.7 parts of antioxidant, 1.6 parts of mineral oil, 1.2 parts of hindered amine light stabilizer, 1 part of ultraviolet absorber, and 1.5 parts of brightener. The antioxidant is antioxidant 1076, the mineral oil is silicone oil, the hindered amine light stabilizer is light stabilizer 944, the ultraviolet absorber is ultraviolet absorber UV-531, and the brightener is fluorescent brightener CBS-127.

[0062] The method for preparing a polypropylene quantum dot diffusion plate comprises the following steps:

[0063] Preparation of nano-microspheres: add 100 parts of water to a container, add 0.3 parts of sodium hydroxide to adjust the pH to 12, heat in a water bath to 60°C, add 0.15 parts of decyl glucoside, add vinyl trimethoxysilane at a rate of 5 drops / s for 10 minutes while stirring, then add 50 drops of 10wt% acetic acid solution, let stand, centrifuge and collect the precipitate, the centrifugal speed is 10000r / min, the centrifugal time is 20min, wash the filter residue with deionized water and anhydrous ethanol several times until neutral, dry to obtain nano-vinyl silicone resin microspheres, the drying temperature is 90°C, and the drying time is 8h; place 30 parts of nano-vinyl silicone resin microspheres in 100 parts of anhydrous ethanol and ultrasonicate for 40 minutes to make the nano-vinyl silicone resin microspheres uniformly dispersed in the anhydrous ethanol, add 0.3 parts of benzoin dimethicone methyl ether, stirring to dissolve benzoin dimethyl ether, then adding 9 parts of thioglycolic acid, stirring under ultraviolet light for 20 minutes, centrifuging and collecting the precipitate, the centrifugal speed is 10000r / min, the centrifugal time is 20min, washing the filter residue with deionized water and anhydrous ethanol for several times until neutral, drying to obtain carboxylated nano vinyl silicone resin microspheres, the drying temperature is 90℃, and the drying time is 8h; adding 20 parts of cobalt acetate to 100 parts of water, and then adding 9 parts of carboxylated nano vinyl silicone resin microspheres to the water, ultrasonicating for 40 minutes, centrifuging and collecting the precipitate, the centrifugal speed is 10000r / min, the centrifugal time is 20min, washing the filter residue with deionized water and anhydrous ethanol for several times until neutral, drying to obtain nano microspheres, the drying temperature is 90℃, and the drying time is 8h;

[0064] 13 parts of the nanospheres are mixed with 61 parts of polypropylene resin, 16 parts of ammonium polyphosphate, 3 parts of pentaerythritol, 1.8 parts of antioxidant, 1.5 parts of mineral oil, 1.2 parts of hindered amine light stabilizer, 1 part of ultraviolet absorber and 1.5 parts of brightener to obtain a mixture a;

[0065] 9 parts of surface carboxylated oil-soluble CdSe / ZnS quantum dots, 66 parts of polypropylene resin, 19 parts of PP-g-MAH resin, 0.7 parts of antioxidant, 1.6 parts of mineral oil, 1.2 parts of hindered amine light stabilizer, 1 part of ultraviolet absorber, and 1.5 parts of brightener are mixed to obtain a mixture b;

[0066] The mixture a and the mixture b are put into a single screw extruder in a mass ratio of 6:1, heated and melted, three-layer co-extruded and embossed to obtain a finished product;

[0067] Among them, the temperatures of each zone of the single-screw extruder are: zone 1 temperature is 190°C, zone 2 temperature is 200°C, zone 3 temperature is 220°C, zone 4 temperature is 220°C, zone 5 temperature is 235°C, zone 6 temperature is 225°C, zone 7 temperature is 220°C, and the die head temperature is 215°C; the production speed is 310kg / h.

[0068] Comparative Example 1

[0069] The difference between this comparative example and Example 2 is that the polypropylene resin in the upper layer and the lower layer formula is increased from 70 parts to 83 parts, and ammonium polyphosphate is not added. The other ingredients and experimental steps are the same as those in Example 2.

[0070] Comparative Example 2

[0071] The difference between this comparative example and Example 2 is that the polypropylene resin in the upper layer and the lower layer formula is increased from 70 parts to 80 parts, and nano-microspheres are not added. The other ingredients and experimental steps are the same as those in Example 2.

[0072] Comparative Example 3

[0073] The difference between this comparative example and Example 2 is that the polypropylene resin in the intermediate layer formula is increased from 74 parts to 89 parts, and PP-g-MAH resin is not added. The other ingredients and experimental steps are the same as those in Example 2.

[0074] Comparative Example 4

[0075] The difference between this comparative example and Example 2 is that in the intermediate layer formula, 7 parts of oil-soluble CdSe / ZnS quantum dots are used to replace 7 parts of surface carboxylated oil-soluble CdSe / ZnS quantum dots, and the other ingredients and experimental steps are the same as those in Example 2.

[0076] Comparative Example 5

[0077] The difference between this comparative example and Example 2 is that there is only an intermediate layer, and the preparation steps of the intermediate layer are the same as those of Example 2.

[0078] The diffuser plates prepared in Examples 1 to 3 and Comparative Examples 1 to 5 were tested.

[0079] Test method:

[0080] Flame retardancy is tested according to UL94 standard;

[0081] Light transmittance and haze are tested according to ASTM D1003 standard;

[0082] The center brightness and average brightness are tested according to GY / T 326-2019 standard;

[0083] Density is tested according to ASTM D792;

[0084] Water barrier performance is usually characterized by water vapor transmission rate (GB / T 1037), which is usually measured at 38℃ / 90RH to measure the mass of water vapor permeating through a unit area of ​​the film, in units of g / (m 2 24h);

[0085] The oxygen barrier performance is characterized by oxygen transmission rate (GB / T 1038), which measures and calculates the volume of oxygen that passes through the sample within 24 hours, in cm 3 / (m 2 ·24h·0.1MPa);

[0086] Brightness and color point detection method: Place the quantum dot diffusion plate under the blue light LED module, and use the CA-310 color analyzer to test the center point brightness, color point X, and color point Y. The current is fixed at 174mA and the voltage is fixed at 8.3V.

[0087] The test results are shown in Table 1.

[0088] Table 1 Diffuser plate performance test results

[0089]

[0090] From the experimental data in Table 1, it can be seen that the flame retardancy of each embodiment of the present application has reached the V0 level, indicating that the flame retardant effect is good, which may be related to the addition of nano-microspheres and ammonium polyphosphate in the upper and lower layers; and the transmittance and haze of each embodiment are both above 80%, the center brightness is above 2000, and the average brightness is above 1900, which may be because quantum dots are added to the middle layer and the quantum dots can be evenly distributed in the system; Continuing to analyze the data from Table 1, the coordinate X offset and color coordinate Y offset of each embodiment are excellent, indicating that the luminescence of each embodiment is stable; the water vapor permeability is less than 0.5g / (m 2 ·24h), oxygen permeability coefficient is less than 0.6cm 3 / (m 2 ·24h·0.1MPa), indicating that each embodiment has high water and oxygen barrier properties; and by comparing embodiments 1 to 3, it can be found that the data of embodiment 2 show that the performance of the diffuser plate prepared therein is the best, which shows that the different ratios of the components have a certain influence on the performance of the diffuser plate. In actual production applications, especially in the pilot-scale scale-up stage, it is necessary to flexibly adjust the ratio of each component according to the actual situation to obtain a product with excellent comprehensive performance.

[0091] Combined with the comparative analysis of the various data of the comparative examples, it can be found that compared with Example 2, the flame retardancy of Comparative Examples 1, Comparative Examples 2 and Comparative Examples 5 is worse. This may be because Comparative Example 1 lacks ammonium polyphosphate and cannot synergize with the nano-microspheres, making the flame retardancy of the diffusion plate worse. The reason why Comparative Example 2 is worse than Comparative Example 1 may be that Comparative Example 2 lacks flame-retardant nano-microspheres. This conclusion can be further verified by Comparative Example 5. Comparative Example 5 only has an intermediate layer and lacks the flame-retardant upper and lower layers, and the flame retardancy is also deteriorated; the transmittance, haze, center brightness, average brightness, coordinate X offset, and color coordinate Y offset of Comparative Examples 3 and 4 are all worse, which may be because the surface of the surface is worse after the lack of PP-g-MAH resin in Comparative Example 3 The compatibility of the surface carboxylated oil-soluble CdSe / ZnS quantum dots with polypropylene deteriorates, and the surface carboxylated oil-soluble CdSe / ZnS quantum dots cannot form a good dispersion in the polypropylene resin, resulting in poor optical performance of the diffuser and unstable luminescence. Comparative Example 4 shows that after the oil-soluble CdSe / ZnS quantum dots replace the surface carboxylated oil-soluble CdSe / ZnS quantum dots, the oil-soluble CdSe / ZnS quantum dots lack carboxyl groups and cannot react with the PP-g-MAH resin, making it impossible for the oil-soluble CdSe / ZnS quantum dots to form a good dispersion in the polypropylene resin, resulting in poor optical performance of the diffuser and unstable luminescence. Continuing to analyze the data of the comparative examples, it can also be found that the water vapor permeability of comparative example 5 exceeds 0.5g / (m 2 24h), the oxygen permeability coefficient exceeded 0.6cm 3 / (m 2·24h·0.1MPa), which may be due to the lack of upper and lower layers. The diffuser with only the middle layer cannot form a "sandwich" structure and cannot physically isolate the quantum dots, making the quantum dots unstable under the influence of the external environment, which leads to poor water and oxygen barrier properties of the diffuser and reduced optical performance.

[0092] In summary, the present application provides a polypropylene quantum dot diffusion plate that has high water and oxygen barrier properties, high flame retardancy, good optical properties, and a stable overall structure.

[0093] The above is only an embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent substitution, improvement, etc. made within the spirit and principle of the present invention should be included in the scope of the claims of the present invention.

Claims

1. A polypropylene quantum dot diffusion plate, characterized in that: The invention comprises an upper layer, a middle layer and a lower layer, wherein the upper layer and the lower layer are located on both sides of the middle layer, and the upper layer and the lower layer have the same components. The upper layer comprises the following components by weight: 61 to 79 parts of polypropylene resin, 7 to 13 parts of nano-microspheres, 10 to 16 parts of ammonium polyphosphate, 1 to 3 parts of pentaerythritol, 1 to 1.8 parts of antioxidant, 0.5 to 1.5 parts of mineral oil, 0.6 to 1.2 parts of hindered amine light stabilizer, and 0.4 to 1 parts of ultraviolet light stabilizer. absorbent, 0.5 to 1.5 parts of brightener; the intermediate layer includes the following components in parts by mass: 66 to 82 parts of polypropylene resin, 11 to 19 parts of PP-g-MAH resin, 5 to 9 parts of surface carboxylation oil-soluble CdSe / ZnS quantum dots, 0.3 to 0.7 parts of antioxidant, 0.6 to 1.6 parts of mineral oil, 0.4 to 1.2 parts of hindered amine light stabilizer, 0.2 to 1 parts of ultraviolet absorber, and 0.5 to 1.5 parts of brightener.

2. The polypropylene quantum dot diffusion plate according to claim 1, characterized in that: The antioxidant is any one of antioxidant 1024, antioxidant 1010 or antioxidant 1076.

3. The polypropylene quantum dot diffusion plate according to claim 1, characterized in that: The mineral oil is silicone oil or liquid paraffin.

4. The polypropylene quantum dot diffusion plate according to claim 1, characterized in that: The hindered amine light stabilizer is any one selected from the group consisting of light stabilizer 622, light stabilizer 770, and light stabilizer 944.

5. The polypropylene quantum dot diffusion plate according to claim 1, characterized in that: The ultraviolet absorber is selected from any one of ultraviolet absorbers UV-327, UV-329, and UV-531.

6. The polypropylene quantum dot diffusion plate according to claim 1, characterized in that: The whitening agent is fluorescent whitening agent CBS-127.

7. A method for preparing a polypropylene quantum dot diffusion plate as claimed in any one of claims 1 to 6, characterized in that: The following steps are involved: preparing the nano-microspheres; The 7-13 parts of nano-microspheres are mixed with 61-79 parts of polypropylene resin, 10-16 parts of ammonium polyphosphate, 1-3 parts of pentaerythritol, 1-1.8 parts of antioxidant, 0.5-1.5 parts of mineral oil, 0.6-1.2 parts of hindered amine light stabilizer, 0.4-1 parts of ultraviolet absorber, and 0.5-1.5 parts of brightener to obtain a mixture a; 5 to 9 parts of the surface carboxylated oil-soluble CdSe / ZnS quantum dots are mixed with 66 to 82 parts of polypropylene resin, 11 to 19 parts of PP-g-MAH resin, 0.3 to 0.7 parts of antioxidant, 0.6 to 1.6 parts of mineral oil, 0.4 to 1.2 parts of hindered amine light stabilizer, 0.2 to 1 parts of ultraviolet absorber, and 0.5 to 1.5 parts of brightener to obtain a mixture b; The mixture a and the mixture b are put into a single screw extruder in a mass ratio of (2 to 6):1, heated and melted, three-layer co-extruded and embossed to obtain a finished product; Among them, the temperatures of each zone of the single-screw extruder are: zone one temperature is 180-190°C, zone two temperature is 190-200°C, zone three temperature is 210-220°C, zone four temperature is 210-220°C, zone five temperature is 225-235°C, zone six temperature is 215-225°C, zone seven temperature is 210-220°C, and the die head temperature is 205-215°C; the production speed is 310kg / h.

8. The method for preparing a polypropylene quantum dot diffusion plate according to claim 7, characterized in that: The preparation of the nano microspheres comprises the following steps: adding 100 parts of water to a container, adding 0.1-0.3 parts of sodium hydroxide to adjust the pH to 10-12, heating in a water bath to 50-60° C., adding 0.05-0.15 parts of decyl glucoside, dripping vinyl trimethoxysilane at a speed of 3-5 drops / s for 5-10 minutes while stirring, then adding 10-50 drops of 10-20wt% acetic acid solution, standing, centrifuging and collecting precipitates, washing the filter residues with deionized water and anhydrous ethanol for several times until neutral, and drying to obtain nano vinyl silicone resin microspheres; placing 10-30 parts of the nano vinyl silicone resin microspheres in 100 parts of anhydrous ethanol for ultrasonication for 20-40 minutes to make the nano vinyl silicone resin microspheres The nano vinyl silicone resin microspheres are uniformly dispersed in the anhydrous ethanol, 0.1 to 0.3 parts of benzoin dimethyl ether are added, stirred to dissolve the benzoin dimethyl ether, 3 to 9 parts of thioglycolic acid are added, stirred for 10 to 20 minutes under ultraviolet light irradiation, centrifuged and precipitates are collected, the filter residue is washed several times with deionized water and anhydrous ethanol respectively until it is neutral, and dried to obtain carboxylated nano vinyl silicone resin microspheres; 10 to 20 parts of cobalt acetate are added to 100 parts of water, 3 to 9 parts of the carboxylated nano vinyl silicone resin microspheres are added to the water, ultrasonicated for 20 to 40 minutes, centrifuged and precipitates are collected, the filter residue is washed several times with deionized water and anhydrous ethanol respectively until it is neutral, and dried to obtain the nano microspheres.

9. The method for preparing a polypropylene quantum dot diffusion plate according to claim 8, characterized in that: The centrifugal speed is 8000-10000 r / min, and the centrifugal time is 10-20 min.

10. The method for preparing a polypropylene quantum dot diffusion plate according to claim 8, characterized in that: The drying temperature is 80-90° C., and the drying time is 6-8 hours.

Citation Information

Patent Citations

  • Preparation method of carboxyl-containing water-soluble CdSeS quantum dots

    CN102093894A

  • Nano-sphere with elements of silicon, cobalt and like as well as synergetic ammonium polyphosphate flame resistant polypropylene material thereof

    CN104744811A

  • Halogen-free flame retardant and resin alloy containing the halogen-free flame retardant

    CN108276749A

  • Inflaming retarding polyphenyl ether resin alloy and preparation method thereof

    CN108485229A

  • Hydrogen bond / bromine bond synergistically assembled bromine bond azopyridine / quantum dot luminescent fiber and preparation method thereof

    CN112796007A